ORGANIZING STUDENT OLYMPIADS AND OTHER COMPETITIONS IN INFORMATION SECURITY: IMPLEMENTING THEIR OUTCOMES INTO THE EDUCATIONAL PROCESS - Petryk, Valentyn (Ukrainian Information Security Research Journal, 2024)
The purpose, methodology, and evaluation system of the International Student Olympiad “Ways and Mechanisms of Protecting Ukraine’s Information Space from Malicious Information and Psychological Influence” and the All-Ukrainian Student Olympiad “Developing Critical Thinking Through Identifying Reliable, Unreliable, Partially Reliable, and Possibly Reliable Information” (also titled “Social Engineering: Ways and Mechanisms of Protection”) are described. The VII International Conference “Protection of Democratic Values and Respect for Human Rights in the Activities of Special Services” is also presented, focusing on the specialization “Russian Aggression Against Ukraine as a Fundamental Threat to Freedom, Democratic Values, and Human Rights: Ukrainian, European, and Global Contexts.” The practical significance of these competitions is demonstrated through the implementation of their outcomes into the educational process of higher education institutions. Proposals are being developed for organizing new student olympiads, particularly in non-technical aspects of information security and in the field of religious studies.